Choosing a Model of Maternity Care: Decision Support Needs of Australian Women. Issue 2 (14th December 2015) - Stevens, Gabrielle; Miller, Yvette D.; Watson, Bernadette; Thompson, Rachel
Abstract: Background: Access to information on the features and outcomes associated with the various models of maternity care available in Australia is vital for women's informed decision‐making. This study sought to identify women's preferences for information access and decision‐making involvement, as well as their priority information needs, for model of care decision‐making. Methods: A convenience sample of adult women of childbearing age in Queensland, Australia were recruited to complete an online survey assessing their model of care decision support needs. Knowledge on models of care and socio‐demographic characteristics were also assessed. Results: Altogether, 641 women provided usable survey data. Of these women, 26.7 percent had heard of all available models of care before starting the survey. Most women wanted access to information on models of care (90.4%) and an active role in decision‐making (99.0%). Nine priority information needs were identified: cost, access to choice of mode of birth and care provider, after hours provider contact, continuity of carer in labor/birth, mobility during labor, discussion of the pros/cons of medical procedures, rates of skin‐to‐skin contact after birth, and availability at a preferred birth location. This information encompassed the priority needs of women across age, birth history, and insurance status subgroups. Conclusions: This study demonstrates Australian women's unmet needs for information that supports them to effectively compare available options for model of maternity care. Findings provide clear direction on what information should be prioritized and ideal channels for information access to support quality decision‐making in practice.